Implementation of childhood obesity prevention and control policies in the United States and Latin America: Lessons for cross‐border research and practice. (5th May 2021) - Pérez‐Escamilla, Rafael; Vilar‐Compte, Mireya; Rhodes, Elizabeth; Sarmiento, Olga L.; Corvalan, Camila; Sturke, Rachel; Vorkoper, Susan
Summary: Progress has been made in the development and widespread implementation of effective interventions to address childhood obesity, yet important challenges remain. To understand how the United States and Latin American countries achieved success in implementing obesity policies and programs (PAPs) and identify improvement opportunities using implementation science principles. We identified three comparative case studies: (1) front‐of‐food package labeling (Mexico and Chile); (2) Open Streets/play streets (Colombia and the United States); and (3) the Baby‐Friendly Hospital Initiative (Brazil and the United States). Information from multiple sources (e.g., scientific and gray literature and key informant interviews) was synthesized to describe barriers, facilitators, and progress of PAPs across RE‐AIM framework dimensions. Evidence‐based advocacy along with political will and evidence of scalability and impact were key for successful launch and implementation of all PAPs. Diverse adaptations of PAP design and implementation had to be done across contexts. Stronger process and impact monitoring and evaluation systems that track equity indicators are needed to maximize the population benefits of these PAPs. Implementation science offers an important contribution toward addressing knowledge gaps, enhancing obesity policy dialogue, and producing transferable lessons across the Americas and, therefore, should be used for research and evaluation during PAP development and throughout the implementation and maintenance phases.